PENGARUH LABEL BPOM, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE PADA SHOPEE WAW.IDN - As Syafa Farahima Diazka (2022)
WAW.idn is an online company that sells skin care products of different brands in the organic mask category and sells them through e-commerce shoppers. However, there are currently problems with the purchase decision of WAW.idn, which has recently been drastically reduced. Therefore, the issue to be determined is whether the BPOM label, price, and product quality affect the purchase decision. And then the purpose of this research is to show and analyze the influence of BPOM label, price and product quality on purchasing decision. The data type used is a quantitative data type, and the user population is consumers who purchase skin care products from Jabodetabek through Shopee WAW.idn. Use a sample of 100 consumers WAW.idn and the required sampling as the method. Partial least squares (PLS) analysis is used with SmartPLS 3.0 software. The results obtained show that BPOM label variables, price, and product quality have a significant positive impact on the purchase decision of skin care products on ShopeeWAW.idn. The limitation of this survey is that the number of respondents is limited, namely 100 respondents. This is because the SmartPLS software used is licensed by the students. Therefore, there are some access restrictions on the use of SmartPLS, one of which is the limited number of respondents.